Tools for instar determination of European caddisfly larvae (Insecta: Trichoptera) - Waringer, Johann (Zootaxa, 2021)
The paper explores the adult-forewing-length to larval-head-width relationship as a basis for instar determination of final instar caddisfly larvae on a family level. In addition, reference data from published sources were used to extract series of percentage-head-width increments and factors-of-increase for penultimate to first instars. This material provides estimates for head widths of earlier instars on the family level.